Screening indoor air quality evaluation in the Lithuanian theatre, music and cinema museum - López-Aparicio, Susana; Grašienė, Rima (Journal of Environmental Engineering and Landscape Management, 2013)
Air pollution is a risk for human health and for the preservation of materials in particular cultural heritage objects. This paper presents the main results obtained in the project carried out by the Lithuanian Theatre, Music and Cinema Museum (LTMCM) and NILU-Norwegian Institute for Air Research. The main goal of the project was to perform a screening study and characterization of the indoor air pollution in the LTMCM. The results are used to assess the indoor air quality with regard to the preservation of cultural heritage objects therein. Measurement of NO2, organic acids (i.e. acetic and formic acids), photo-oxidant effects of the environment, climate (temperature and relative humidity) and particulate matter deposition were performed in different indoor locations. Low concentration of outdoor generated pollutants such as NO2 was found in storage rooms whereas higher concentrations were determined in the in the exhibition area. The results indicate that the building envelope does not protect effectively against infiltration of outdoor pollutants such as NO2 and particles. Very high concentration of indoor generated pollutants such as acetic acid was found in one storage room with a significant source.First published online: 11 Oct 2012